Acute and Sub Acute Toxicity Study on Siddha Drug Thennangal Thiravagam - Aruna, V (International Journal of Pharmaceutical & Biological Archive, 2014)
Acute and Sub Acute Toxicity Study on Siddha Drug Thennangal Thiravagam